Modulation of anti-cardiac fibrosis immune responses by changing M2 macrophages into M1 macrophages - Shiqi Chen; Kan Wang; Zhengfeng Fan; Tingwen Zhou; Rui Li; Bingxia Zhang; Jie Chen; Jiangyang Chi; Keke Wei; Jincheng Liu; Zongtao Liu; Jingwei Ma; et al. (BMC, 2024)
Abstract Background Macrophages play a crucial role in the development of cardiac fibrosis (CF). Although our previous studies have shown that glycogen metabolism plays an important role in macrophage inflammatory phenotype, the role and mechanism of modifying macrophage phenotype by regulating glycogen metabolism and thereby improving CF have not been reported. Methods Here, we took glycogen synthetase kinase 3β (GSK3β) as the target and used its inhibitor NaW to enhance macrophage glycogen metabolism, transform M2 phenotype into anti-fibrotic M1 phenotype, inhibit fibroblast activation into myofibroblasts, and ultimately achieve the purpose of CF treatment. Results NaW increases the pH of macrophage lysosome through transmembrane protein 175 (TMEM175) and caused the release of Ca2+ through the lysosomal Ca2+ channel mucolipin-2 (Mcoln2). At the same time, the released Ca2+ activates TFEB, which promotes glucose uptake by M2 and further enhances glycogen metabolism. NaW transforms the M2 phenotype into the anti-fibrotic M1 phenotype, inhibits fibroblasts from activating myofibroblasts, and ultimately achieves the purpose of treating CF. Conclusion Our data indicate the possibility of modifying macrophage phenotype by regulating macrophage glycogen metabolism, suggesting a potential macrophage-based immunotherapy against CF. Graphical Abstract